The influence of methotrexate-related transporter and metabolizing enzyme gene polymorphisms on peri-engraftment syndrome and graft-versus-host disease after haplo-hematopoietic stem cell transplantation in pediatric patients with malignant hematological diseases - Ji, Qi; Zhang, Yongping; Hu, Yixin; Liu, Lixia; Cao, Shanbo; Gao, Li; Li, Bohan; Tian, Yuanyuan; Kong, Lingjun; Wu, Shuiyan; Ling, Jing; Xiao, Peifang; et al. (Frontiers in Immunology, 2023)
Background: Methotrexate (MTX), utilized as a graft-versus-host disease (GvHD) prophylactic agent in allogeneic hematopoietic stem cell transplantation (allo-HSCT), has been proven to effectively decrease the occurrence of the peri-engraftment syndrome (Peri-ES) and acute GvHD (aGvHD). Changes in the pharmacodynamics of MTX are closely associated with gene polymorphisms in genes encoding drug-metabolizing enzymes and transporters. Nevertheless, the current studies mainly concentrate on leukemia or autoimmune diseases, and limited studies on the allo-HSCT were reported. Methods: Here, we retrospectively assessed the relationship between MTX-related transporter and metabolizing enzyme gene polymorphisms, clinical characteristics and outcomes in 57 pediatric patients, who received haploid HSCT (haplo-HSCT), with malignant tumors at a single center. Results: We discovered all gene polymorphisms were in Hardy-Weinberg equilibrium in our cohort. We discovered a significant correlation between platelet recovery time and ABCB1 (1236C>T) (P = 0.042). Compared with SLCO1B1 (1865+4846T>C) TT, patients with SLCO1B1 (1865+4846T>C) TC/CC had the increased incidence of Peri-ES (P = 0.030). Based on the multivariate Cox analysis, we discovered that SLCO1B1 (1865+4846T>C) TT genotype was an independent protective factor for Peri-ES morbidity (HR = 0.464, P = 0.031) and the dose of mononuclear cells reinfused was significantly correlated with II-IV aGvHD (HR = 2.604, P = 0.039). Conclusion: In summary, our findings prove that the host’s genotypes might modify the risk of developing Peri-ES, contribute to a better understanding of the inter-individual difference in efficacy, and facilitate the development of individualized approaches to GvHD prophylaxis.